The Length of Days : An Urban Ballad - Rafeyenko, Volodymyr; Forrester, Sibelan; Shore, Marci (Cambridge, Massachusetts : Harvard University Press, 2023)
In The Length of Days, featuring a wild cast of characters, Rafeyenko combines poetry and wicked humor with elements of magical realism. The novel is set in 2014, mostly in the composite Donbas city of Z--an uncanny foretelling of what this letter has come to symbolize since February 2022, when Russia launched a full-scale invasion of Ukraine.
Frontmatter -- Contents -- The Length Of Days: An Urban Legend -- In the City of Z, a Bathhouse Where What Happened Can Unhappen: An Afterword to The Length of Days -- On Truth, Dignity, and Being Human above All: Volodymyr Rafeyenko in Correspondence with Marci Shore -- Notes
Description based on online resource; title from digital title page (viewed on May 18, 2023).
JSTOR
Keywords: Russo-Ukrainian War, 2014- -- Fiction; Magic realism (Literature); Donets Basin (Ukraine and Russia) -- Fiction; Guerre russo-ukrainienne, 2014- -- Romans, nouvelles, etc; Réalisme magique (Littérature); Donbass (Ukraine et Russie) -- Romans, nouvelles, etc; LITERARY CRITICISM / General; Magic realism (Literature); Europe -- Donets Basin; Since 2014; Electronic books; Fiction